Widespread Exposures of Extensive Clean Shallow Ice in the Midlatitudes of Mars. Issue 3 (5th March 2021) - Dundas, Colin M.; Mellon, Michael T.; Conway, Susan J.; Daubar, Ingrid J.; Williams, Kaj E.; Ojha, Lujendra; Wray, James J.; Bramson, Ali M.; Byrne, Shane; McEwen, Alfred S.; Posiolova, Liliya V.; Speth, Gunnar; et al.
Abstract: Although ice in the Martian midlatitudes is typically covered by a layer of dust or regolith, it is exposed in some locations by fresh impact craters or in erosional scarps. In both cases, the exposed ice is massive or excess ice with a low lithic content. We find that erosional scarps occur between 50° and 61° north and south latitude and that they are concentrated in and near Milankovič crater in the northern hemisphere and southeast of the Hellas basin in the southern hemisphere. These may represent locations of particularly thick or clean bodies of ice. Pits created by retreat of the scarps represent sublimation‐thermokarst landforms that evolve in a manner distinct from other ice‐loss landforms on Mars. New impact craters reveal that clean subsurface ice is widespread at middle‐ and high‐latitudes in both hemispheres at depths less than 1 m. Both the depth to ice and the ice content appear to exhibit significant variability over tens to hundreds of meters. The lowest‐latitude exposed ice is near 39°N and is at the edge of a region where impact exposures between 40° and 50°N are common, consistent with other indications of a high ice content. This lowest‐latitude ice may be currently unstable and subliming. Impact craters on lineated valley fill excavate ice blocks that may represent the top of debris‐covered glacial ice. Together, these landforms indicate widespread, clean subsurface ice at middle‐latitudes on Mars. The distribution and properties of this ice could provide information about past climate conditions. Plain Language Summary: Ice occurs at the surface near the north and south poles of Mars, but in the midlatitudes it is usually buried beneath rocks and dust. Impact craters and erosion expose the ice in some places. At these locations, the ice is generally clean, with little dust or rocky material embedded within it, in contrast with pore ice filling in voids in soil. The erosional exposures are concentrated in and near Milankovič crater in the northern hemisphere and southeast of the Hellas basin in the southern hemisphere and occur at a narrow range of latitudes. These may be locations of particularly thick, clean ice. Impact craters reveal that some amount of such subsurface ice is widespread. The craters help to define the lowest latitude where ice is present and how deeply it is buried, which could provide information about the history of the climate on Mars. Key Points: Subsurface ice with a low lithic content is exposed in scarps and around new impact craters at mid‐latitude and high‐latitude on Mars Ice‐exposing scarps indicate localized accumulations of thick clean ice and are concentrated in specific regions of Mars Impact craters help define the distribution of subsurface ice, and indicate a region of high ice content at relatively low‐latitude